1998
DOI: 10.1191/096120398678919787
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated connective tissue diseases: the clinical and serological profiles of 91 patients followed for at least 1 year

Abstract: The objective of this work was to evaluate the clinical and serological profiles of patients with undifferentiated connective tissue diseases (UCTD) who had been followed for at least 1 year. The retrospective analysis (197495) was based on UCTD patients diagnosed on the basis of clinical manifestations suggestive of a connective tissue disease, and the presence of at least one non-organ-specific autoantibody. A total of 91 patients were evaluated. The condition of 79 remained stable during the follow up, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 18 publications
3
60
0
6
Order By: Relevance
“…The published prospective studies [12][13][14][15][16][17][18] found an evolving frequency that varies from 5% to 68% of patients. According to this data, it is estimated that 20-40% of patients with early UCTD will develop a definite CTD [11].…”
Section: Discussionmentioning
confidence: 99%
“…The published prospective studies [12][13][14][15][16][17][18] found an evolving frequency that varies from 5% to 68% of patients. According to this data, it is estimated that 20-40% of patients with early UCTD will develop a definite CTD [11].…”
Section: Discussionmentioning
confidence: 99%
“…The study population consisted of 57 Caucasian patients with the following connective tissue diseases: Sjögren's syndrome (SS), systemic lupus erythematosus (SLE), systemic sclerosis (SSc), diagnosed according to the criteria of the American College of Rheumatology (formerly, the American Rheumatism Association) and the European Community Study Group (11)(12)(13), undifferentiated connective tissue disease (UCTD) (14), and mixed connective tissue disease (MCTD) (15). Patients were grouped according to positivity (n ϭ 31) and negativity (n ϭ 26) for anti-Ro/SSA antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…La popolazione di pazienti in esame è già stata precedentemente descritta (7,14). Si tratta di una coorte di 91 pazienti con diagnosi di UCTD della durata di almeno un anno seguiti presso la nostra Unità Operativa.…”
Section: Materiali E Metodiunclassified
“…Le manifestazioni cliniche e sierologiche presentate dai pazienti sono state raccolte in apposite cartelle cliniche. I dati relativi alle manifestazioni cliniche e sierologiche presenti alla prima osservazione erano già disponibili dalla analisi effettuata in occasione dei precedenti studi (7,14). La ricerca degli autoanticorpi è stata effettutata utilizzando tecniche validate (7,14).…”
Section: Materiali E Metodiunclassified
See 1 more Smart Citation